Application Of Vegetable And Fruit Waste Liquid Organic Fertilizer (POC) as Nutrition for Red Chili Pepper Plant Growth (Capsicum Annuum L.) - Ananto Ananto; Andi Alatas (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
The purpose of this study was to determine the effect of liquid organic fertilizer in increasing the growth of red chili pepper plants because inorganic fertilizers utilization was widespread among farmers. Thus, the idea emerged for the application of liquid organic fertilizers. The application time and place of liquid organic fertilizer were carried out in the experimental field of STIPER Sawahlunto Sijunjung. The design used was a Randomized Block Design (RAK) with five levels of treatment and five groups in order to obtain 25 experimental units. The application of market waste POC on red chili pepper plants has not significantly affected the growth of red chili pepper plants. Treatment of market waste POC at a concentration of 500 (ml/L) is the optimal dose/dose for increasing the number of leaves by 115 strands (control 63 strands) and the increase in plant height by 71.40 cm (control 55.40 cm). In general. POC applications of market waste are still unable to achieve optimal growth and yields, and this is because there is no addition of nutrients to plants to support growth.